Iterative construction and optimization of fuzzy models - Goléa, Noureddine; Benmahammed, Khier (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a constructive approach to the fuzzy model selection problem is developed. First, the selection of membership functions is decoupled from parameter calculations using an orthogonalization procedure. Since each membership function depends only on its own parameters, the selection of rules is performed in a sequential manner.
Keywords: fuzzy approximation; decoupled learning; iterative optimization